Impact of Agricultural Input Subsidy Assistance Card Program on Farm Production in Rajbari District of Bangladesh - Sarma, Paresh Kumar; Hossain, Anwar (Journal of the Bangladesh Agricultural University, 2020)
This paper aims to use a novel version of an endogenous switching regression model to examine the impact of agricultural input subsidy assistance card on-farm productivity in Bangladesh. A multistage random sampling technique was employed to select a total of 400 farm households including 181 (45.25%) adaptors and 219 (54.75%) non-adaptors and interviewed by using pre-canvassing structured survey questionnaires. Also, FGDs and KIIs have been conducted to get qualitative information. The descriptive statistics, probit regression-double hurdle model, endogenous switching regression (ESR) technique, and propensity score matching approach were used to analyze the collected data. The ESR model supported by binary and PSM was used to empirically assess the impact of subsidy card adaptors on outcome variables. The results revealed significant production enhancing effects of agricultural input subsidy on-farm production and farm income in Bangladesh only under the assistance of input subsidy card. The findings also showed higher production and incomes for those participating in the program. However, a comprehensive input subsidy assistance card package is certainly a requirement for increasing production and income. As the adoption of input subsidy assistance card seems enhancing farm productivity, the study recommends increased coverage of the subsidy program, extension advocacy and opening up to ensure agricultural productivity and increased farm incomes. This study illustrates how agricultural input subsidy assistance cards can improve farm production and income in Bangladesh. J Bangladesh Agril Univ 18(3): 688–699, 2020 https://doi.org/10.5455/JBAU.104820